Analisis Reformasi Tata Kelola Administrasi Pemerintahan (Studi Kasus Provinsi Jawa Barat) - Sudrajat, Yayat (Universitas Batanghari Jambi, 2024)
The challenges of governance in the era of globalization are becoming increasingly complex, particularly in West Java Province, which faces public demands for efficiency, transparency, and accountability in public services. Although governance reforms have been implemented, obstacles such as complex bureaucracy, a lack of accountability, and rapid socio-economic changes continue to impact service quality. This study aims to analyze the impact of administrative governance reforms on the efficiency of public services. The main focus of this research is on the changes in transparency and public participation resulting from the implemented reforms, as well as the primary challenges faced in their implementation, including bureaucratic obstacles and technology adoption. The research employs a qualitative approach. Data were collected through 30 in-depth interviews with 10 government officials, 10 business actors, and 10 members of the general public. Additionally, focus group discussions (FGDs) were conducted involving 8-12 participants to gain deeper insights into their experiences related to governance reforms. Data analysis was performed using a thematic approach. The findings indicate that governance reforms in West Java Province have accelerated public administrative services, particularly through digitalization, which has reduced processing times for permits. However, challenges remain, such as limitations in human resources and technology, resistance to change among civil servants, and discrepancies in policy implementation across regions. Therefore, enhancing employee training and simplifying bureaucratic procedures are essential to ensure the sustainability of these reforms.